Analisis Pengaruh Motivasi dan Tunjangan Terhadap Produktifitas Kerja Karyawan : Studi Pada Salesman Retail PT. Surya Madistrindo – Area Office Malang - Agus Wiastono; Awanto twui wibowo; YUNITA (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
This study aimed to find out how work motivation affects employee productivity and how work motivation affects employee productivity at PT. Surya Madistrindo. This was a quantitative observational study. The information was gathered through questionnaires and then evaluated using multiple regression analysis in SPSS 24.0 for Windows, which contains a t-test. Work incentives positively and significantly impacted employee output, as evidenced by a positive regression coefficient of 7.672, a t-test value of 7.813 > t-table = 2.042, and a probability value of 0.000 = 0.05. The effect of job enthusiasm on staff output at Teh Bunga Teratai Company was demonstrated by a coefficient of determination of 0.668. This indicates that job motivation influences 66.8% of workers’ productivity.